Grid division and partial schematic diagram of facilities in the main urban area of Beijing. - Shifeng Wu (16612230) (2025)
This map was vectorized based on the standard map with the review number of Jing S (2022) 019, accessed October 22-25, 2020, at https://beijing.tianditu.gov.cn/bzdt/.